Analysis of single fly ash particles for application to environmental geochemistry - Rousseau, Pierre D. S.(Pierre Daniel Stuart) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1997.